Human Resource Strategic to Maintain Waste Management in Organization - Ismail, Fadillah; Mardhiyah Nor Aziz, Ainul; Md. Syukri Wan Mohamad Ali, Wan; Mohd Yusof, Halimah (International Journal of Engineering and Technology, 2018)
The time constraint to concentrate on human resource management and lack of knowledge for the key strategic management of human resource would constrain the expand of the needs for its execution. The objective or motivation behind this study is to investigate the relationship and practice of strategic human resource management, the awareness of the exploration on strategic human resource management improves and professional conduct on waste management in organization. This investigation enhances to the logical group of research to fill the gap that as of now exists in organization. Waste management is chosen as the concentration of this investigation in relationship between strategic human resource management and sustainable competitive advantage. Thus, this research is important to manager’s level and academia for benefit table to business settings further enhancement.
Keywords: Strategic Human Resource Management; Waste Management; Sustainable Competitive Advantage